2005
DOI: 10.1007/s00702-005-0330-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between body weight of newborn rats and density of serotonin transporters in the frontal cortex at adulthood

Abstract: Persisting alterations in monoaminergic innervation patterns have been observed following various environmental manipulations and neuro-psychopharmacological treatments during fetal or early postnatal life. The present study investigates the question how differences in initial growth conditions at birth might interfere with subsequent development of both serotonergic and noradrenergic innervation in the rat frontal cortex (FC) and brain stem. For this purpose, newborn rat littermates were divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…levels of 5-HT transporter in the frontal cortex [148]. Taken together, this suggests that disruption of 5-HT production in the gut and brain, with early exposure to SSRIs at a time when the neonate is very sensitive to toxins [138], may produce long term differences in growth, metabolism, and mood via changes in 5-HT production and related physiology of the brain-gut axis.…”
Section: Growth Brain-gut Axis Development and The Serotonergic Systemmentioning
confidence: 88%
“…levels of 5-HT transporter in the frontal cortex [148]. Taken together, this suggests that disruption of 5-HT production in the gut and brain, with early exposure to SSRIs at a time when the neonate is very sensitive to toxins [138], may produce long term differences in growth, metabolism, and mood via changes in 5-HT production and related physiology of the brain-gut axis.…”
Section: Growth Brain-gut Axis Development and The Serotonergic Systemmentioning
confidence: 88%
“…For instance, rhesus macaques that experienced high rates of rejection from their mothers soon after birth have lower levels of 5-HTT binding which is independent of 5-HTT genotype [55]. Another study compared SLC6A4 density in adulthood as a function of common natural variation in birth weight in rats [56]. It was found that rats which were 10-20% lighter at birth than their littermate had reduced 5-HTT density in the frontal cortex in adulthood, while there were no differences in noradrenaline transporter density.…”
Section: (B) Slc6a4 and Integrity Of The Brainmentioning
confidence: 99%
“…Birth weight (BW) can be used as an overall index of the in utero environment [1,2,3,4]. Research has shown that individuals born with a very low BW (<1,500 g) have smaller brains than controls from infancy to early adulthood [5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%